PATH-67. RECOMBINANT INTERLEUKIN-7 ENHANCES THE ANTI-TUMOR IMMUNITY OF A DENDRITIC CELL VACCINE IN A MURINE MALIGNANT GLIOMA. (11th November 2019) - Hooy Oh, Sol; Ahn, Stephen; Sung Park, Jae; Kil Hong, Yong; Jeon, Sin-Soo
Abstract: BACKGROUND: Dendritic cell (DC)-based vaccines have been suggested as one of the promising immunotherapies for treating various cancers, including glioblastoma. We already developed a novel vaccination protocol with peptide-loaded DCs followed by a mixture of synthetic peptides, polyinosine- polycytidylic acid (poly-IC) and anti-CD40 antibodies (Trivax) in a melanoma mouse model. However, in a glioma mouse model, therapeutic efficacy is not as much as enough maybe due to relatively low antigenicity and blood brain barrier. MATERIAL AND METHODS: IL-7, which is one of the most important cytokines to expand and develop T cells with anti-tumor immunity, was co-administrated intravenously with Trivax in an orthotopic murine malignant glioma. RESULTS: Co-administration of the Trivax and recombinant IL-7 (Trivax7) increased the number of survivin specific T cells measured using ELISPOT assay and the population of central memory T cells, comparing with administration of Trivax. The tumor size of orthotopic mouse model in Trivax 7 group was smaller than those of Trivax only group. Finally, overall survival in Trivax 7 was longer than those of Trivax only. In addition, there was a prolonged survival of antigen-specific T cells in Trivax7 group than Trivax only group. CONCLUSION: In summary, our novel combinational immunotherapy may overcome the limitations of current cell-based cancer vaccines and could be applicable for the treatment of glioblastoma patients.